(untitled) (The Research of Medical Science Review, 2025)
Thalassemia, a hereditary blood disorder, poses a major public health concern in Pakistan, where consanguineous marriages and limited awareness contribute to a growing burden of disease. This study explores the level of awareness regarding thalassemia and its impact on the health-related quality of life (HRQoL) among pregnant women in Lahore, Pakistan. Conducted at Shalamar Hospital using a cross-sectional design, the study surveyed 100 pregnant women attending antenatal clinics through a structured questionnaire and the SF-36 health survey. Results revealed that while 65% of participants were aware of thalassemia, only 30% had undergone screening, and just 50% could identify its symptoms. Awareness of complications, treatment options, and support resources was similarly limited. Despite this, a strong majority (85%) supported mandatory screening, and 90% emphasized the need for awareness programs. Regression analysis showed a significant association between thalassemia awareness and HRQoL outcomes, particularly regarding mental well-being and disease-related anxiety. The findings highlight critical knowledge gaps, poor provider-patient communication, and systemic barriers, including insufficient educational outreach and healthcare infrastructure. Socio-cultural factors, particularly consanguineous marriages and religious beliefs, further impede prevention efforts. The study underscores the urgent need for comprehensive educational interventions, mandatory screening policies, enhanced genetic counseling services, and the development of community-based support systems. These strategies are essential to empower women, prevent new cases, and improve maternal and fetal health outcomes. Future research with larger, more diverse populations is recommended to strengthen public health policy and reduce the national burden of thalassemia.